Differentiated vulvar intraepithelial neoplasia long‐term follow up and prognostic factors: An analysis of a large historical cohort - Niccolò Gallio; Mario Preti; Ronald W. Jones; Fulvio Borella; Linn Woelber; Luca Bertero; Sara Urru; Leonardo Micheletti; Federica Zamagni; Federica Bevilacqua; Pierluigi Tondo; Benedetta Pollano; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Differentiated vulvar intraepithelial neoplasia (dVIN) is a high‐risk preinvasive vulvar lesion and precursor of human papillomavirus‐independent vulvar squamous cell carcinoma (VSCC). Due to its rarity, literature data on its malignant potential are scant. The aim of the study is to assess the risk of developing VSCC in patients surgically treated for dVIN not associated with VSCC (solitary dVIN) and the risk of VSCC recurrence in patients treated for dVIN associated with VSCC (dVIN‐VSCC) at first diagnosis. Material and methods A historical cohort study was performed in a northern Italy referral center for vulvar neoplasms. All consecutive women surgically treated for histologically confirmed dVIN from 1994 to 2021 were collected. Primary outcome was cancer risk or recurrent cancer risk, secondary outcomes were risk factors associated with VSCC development or recurrence. Kaplan–Meier method and log‐rank test were used to estimate cancer risk or recurrent cancer risk differences and uni‐ and multivariate Cox regression analyses to identify risk factors associated with VSCC development in solitary dVIN and recurrence of dVIN‐VSCC. Results Seventy‐six patients with dVIN at preoperative biopsy were included: at excisional specimens 44 were solitary dVIN and 32 were dVIN‐VSCC. The absolute risk of VSCC development after solitary dVIN treatment was 43.2% with median time to to VSCC diagnosis of 25.4 months (range 3.5–128.0 months). VSCC recurrence absolute risk in treated dVIN‐VSCC patients was 31.3% with median time to VSCC recurrence of 52.9 months (range 6.5–94.8 months). At uni‐ and multivariate regression analyses, only compliant topical ultrapotent corticosteroid treatment after solitary dVIN excision showed an ability to prevent VSCC development. No protective effect by corticosteroid treatment was shown for VSCC recurrence in dVIN‐VSCC patients. Smoking was associated with higher cancer recurrence risk in dVIN‐VSCC patients on both uni‐ and multivariate regression analyses. Conclusions Patients with dVIN have a high risk of developing both primary and recurring VSCC. Early recognition, long‐term follow up, and compliant ultrapotent topical corticosteroid treatment are recommended.